Middle East Transitions A Long, Hard Road - Yusuf, Shahid (International Monetary Fund, 2014)
Since the onset of the Arab Spring, economic uncertainty in Egypt, Jordan, Libya, Morocco, Tunisia, and Yemen (Arab Countries in Transition, ACTs) has slowed already sluggish growth; worsened unemployment, particularly of youth; undermined business confidence, affected tourist arrivals, and depressed domestic and foreign direct investment. Furthermore, political and social tensions have constrained reform efforts. Assessing policy options as presented in the voluminous literature on the Arab Spring and based on cross-country experience, this paper concludes that sustainable and inclusive growth calls for a two pronged approach: short term measures that revive growth momentum and partially allay popular concerns; complemented with efforts to adjust the public's expectations and prepare the ground for structural reforms that will deliver the desired longer tem performance